2021
DOI: 10.1175/jcli-d-20-0194.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and Trends of Drivers of Mesoscale Convective Systems in Southern West Africa

Abstract: Mesoscale convective systems (MCSs) are the major source of extreme rainfall over land in the tropics and are expected to intensify with global warming. In the Sahel, changes in surface temperature gradients and associated changes in wind shear have been found to be important for MCS intensification in recent decades. Here we extend that analysis to southern West Africa (SWA) by combining 34 years of cloud-top temperatures with rainfall and reanalysis data. We identify clear trends in intense MCSs since 1983 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 72 publications
3
18
0
Order By: Relevance
“…These trends are largely positive across SWA ( Fig. 1 B and C ), consistent with earlier large-scale studies ( 27 , 29 ). There are, however, strong within-region variations, with a tendency for areas with weak LST trends to have weaker trends in convective activity ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These trends are largely positive across SWA ( Fig. 1 B and C ), consistent with earlier large-scale studies ( 27 , 29 ). There are, however, strong within-region variations, with a tendency for areas with weak LST trends to have weaker trends in convective activity ( Fig.…”
Section: Resultssupporting
confidence: 90%
“… 26 ), which are typically triggered in the afternoon and propagate westwards. There are important, large-scale, positive trends in intense MCSs in SWA ( 27 ). More intense African MCSs have been linked to increasing meridional temperature gradients ( 27 29 ), while recent decades have seen more frequent MCSs across SWA in the second rainy season ( 27 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2017), who used 35 years of satellite observations and rain gauge readings from the West African Sahel to reveal a persistent increase in the frequency of the most intense MCSs over this period: this was inferred from a trend of 0.78C/decade in cloud top temperatures. Intensification of MCSs was restricted to a narrow Sahelian belt in the months of June to September but extends to the Guinea coast in the spring (Klein et al ., 2021). This increase in the frequency of MCSs is only weakly related to the multi‐decadal recovery of the Sahel annual rainfall but exhibits a similar trend to global land temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) found that rain rates scaled with the product of time‐of‐storm total column water and in‐storm vertical velocity. However, despite pre‐storm wind shear modulating in‐storm vertical velocity and the resulting cloud‐top temperatures, they found no direct correlation between wind shear and precipitation rates in CP4A, in contrast to observations for the Gulf of Guinea (Klein et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%